Pusa Sona – A new variety of onion - Joshi, Subodh; Islam, Sabina; Khar, Anil; Tomar, B S; Pandita, V K (Indian Horticulture, 2020)
Onion bulbs are valued for their everyday use in Indian culinary. Besides it has export value and medicinal properties. Adoption of newly developed varieties for commercial cultivation will help in improving productivity. Onion variety Pusa Sona, developed at Division of Vegetable Science has been notified recently for commercial cultivation. Pusa Sona is suitable for commercial cultivation during rabi season in zone II , comprising Delhi, Rajasthan, Haryana, Jammu region of J&K and Punjab.